Management of Teacher Professional Competence Improvement at MTsN 2 Palangka Raya City - Murjani Murjani; Istanto Istanto; Rita Sukaesih; Arbainsyah Arbainsyah; Ade Tutty R Rossa (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
Teachers are an essential element in the success of education. Therefore, the management of teacher professional competency improvement must be owned by a teacher. This study aims to determine the management of improving the professional competence of teachers at MTsN 2 Palangka Raya City. This research uses a case study descriptive method to get an overview of the management of improving the professional competence of teachers at MTsN 2 Palangka Raya City. The responses in this study were from the Head of the School, the Head of Administrative Affairs, and the Board of Teachers of MTsN 2 Palangka Raya City. The results of the study found that the management of increasing teacher professional competence carried out at MTsN 2 Palangka Raya City had been carried out based on management principles which included planning, organizing, implementing, and by regulations and guidelines regarding teacher professional competence, but there were still obstacles in efforts to increase professional competence teachers, including the low motivation of teachers in developing sustainable professionalism, especially in terms of making scientific papers and scientific publications. With the management of improving the professional competence of teachers, the number of publications will increase in the creation of scientific work at MTsN 2 Palangka Rata City.